Viewing distance matter to perceived intensity of facial expressions - Gerhardsson, Andreas; Högman, Lennart; Fischer, Håkan (Frontiers in Psychology, 2015)
In our daily perception of facial expressions, we depend on an ability to generalize across the varied distances at which they may appear. This is important to how we interpret the quality and the intensity of the expression. Previous research has not investigated whether this so called perceptual constancy also applies to the experienced intensity of facial expressions. Using a psychophysical measure (Borg CR100 scale) the present study aimed to further investigate perceptual constancy of happy and angry facial expressions at varied sizes, which is a proxy for varying viewing distances. Seventy-one (42 females) participants rated the intensity and valence of facial expressions varying in distance and intensity. The results demonstrated that the perceived intensity of the emotional facial expression was dependent on the distance of the face and the person perceiving it. An interaction effect was noted, indicating that close-up faces are perceived as more intense than faces at a distance and that this effect is stronger the more intense the facial expression truly is. The present study raises considerations regarding constancy of the perceived intensity of happy and angry facial expressions at varied distances.